INTERDISCIPLINARY INTEGRATION IN QUR’ĀNIC EXEGESIS;: A Study of Tafsīr Safīnah Kallā Saya’lamūn Through the Lens of Tadākhul al-Ma‘ārif - Delta Yaumin Nahri; Putri Alfia Halida; Ihwan Agustono; Muhimmatus Sa'adah (PAPPASANG, 2026)
Tafsīr Safīnah Kallā Saya’lamūn has a systematic structure and an interpretive style that reflects a clear interdisciplinary orientation. However, most existing studies remain descriptive and have not examined in depth how interdisciplinary engagement operates within its interpretive framework using a specific theoretical lens. This study addresses that gap by analyzing the forms and levels of interdisciplinary interaction in the chapter Fabiẓālik Fartaqib wa Biẓālik Faqtarib through the framework of tadākhul al-ma‘ārif, focusing on Q.S. Āli ‘Imrān (3): 101, Q.S. al-Baqarah (2): 155–156, and Q.S. Āli ‘Imrān (3): 120. Using a qualitative library method with content analysis, this study identifies two main patterns. First, a conceptual integration between Qur’ānic exegesis and Sufi thought, producing ethical and spiritual meanings such as prayer, remembrance of the Prophet, patience, and moral resilience. Second, a contextual-illustrative use of scientific and technological ideas, especially the metaphor of “fire” as energy, to relate Qur’ānic messages to contemporary life. However, these interactions remain fragmented and not yet methodologically unified. This study proposes a typology of interdisciplinary engagement in Qur’ānic interpretation based on tadākhul al-ma‘ārif to clarify different modes of knowledge interaction in modern tafsir